An In Situ Carbonization–Replication Method to Synthesize Mesostructured WO3/C Composite as Nonprecious‐Metal Anode Catalyst in PEMFC1. Issue 2 (30th November 2012) - Cui, Xiangzhi; Hua, Zile; Wei, Chenyang; Shu, Zhu; Zhang, Liangxia; Chen, Hangrong; Shi, Jianlin
Abstract A meostructured WO3/C composite with crystalline framework and high electric conductivity has been synthesized by a new in situ carbonization–replication route using the block copolymer (poly(ethylene glycol)‐block‐poly(propylene glycol)‐block‐poly(ethylene glycol)) present in situ in the pore channels of mesoporous silica template as carbon source. X‐ray diffraction, X‐ray photoelectron spectroscopy, transmission electron microscopy, thermogravimetry differential thermal analysis, and N2 adsorption techniques were adopted for the structural characterization. Cyclic voltammetry, chronoamperometry, and single‐cell test for hydrogen electrochemical oxidation were adopted to characterize the electrochemical activities of the mesoporous WO3/C composite. The carbon content and consequent electric conductivity of these high‐surface‐area (108–130 m2 g−1) mesostructured WO3/C composite materials can be tuned by variation of the duration of heat treatment, and the composites exhibited high and stable electrochemical catalytic activity. The single‐cell test results indicated that the mesostructured WO3/C composites showed clear electrochemical catalytic activity toward hydrogen oxidation at 25 °C, which makes them potential non‐precious‐metal anode catalysts in proton exchange membrane fuel cell.